Kepemimpinan Sektoral Indonesia di ASEAN: Studi Atas Kontra-Terorisme - Nurul Aulia; Maya Salvina (Universitas Medan Area, 2025)
This study intends to analyze Indonesia’s sectoral leadership in counter-terrorism in Southeast Asia through ASEAN framework. Terrorism, radicalism, and violent extremism constitute significant non-traditional threats in the region. Employing the concept of sectoral leadership, this research examines the extent to which Indonesia has played a leadership in specific issue areas within ASEAN. Using a qualitative approach through desk research and interviews, the study finds that Indonesia fulfills the four key elements of sectoral leadership: material and institutional capabilities, political commitment, normative authority, and legitimacy from other states. Indonesia’s leadership is reflected in diplomatic initiatives such as the ASEAN Plan of Action to Prevent and Counter the Rise of Radicalisation and Violent Extremism (ASEAN PoA PCRVE) 2018-2025 and Bali Work Plan 2019-2025. The finding suggest that Indonesia leadership is contributing to institutional development and strengthening of regional security cooperation. The study underscores the relevance of sectoral leadership as a conceptual lens for understanding the dynamic of states roles in regional organizations, particularly in the Global South.